Towards a better understanding of the value of physical fitness testing within the identification and development of youth soccer players - Dugdale, J. H. (University of Stirling, 2019)
The aim of this thesis is to better understand how physical fitness testing may be used to contribute towards talent identification (TI) processes of youth soccer players, and how valid physical fitness testing methods may be when implemented within talent development (TD) of various samples of youth soccer players. In the first study of this thesis (Chapter 3), discriminative ability of a comprehensive battery of commonly-used field-based fitness tests relating to change of direction (COD), sprinting, strength, and jumping performance was assessed, alongside examining reliability of all measures across a broad range of ages. Findings from this initial study suggest that a comprehensive fitness test battery can discriminate between distinct performance standards with reasonable accuracy; Chi2 (7) = 101.646, p<0.01, with 70.2% of players being correctly classified. However, may lack the ability to differentiate between more homogenous groups of youth soccer players. Moreover, this first study identified potential lower reliability of COD tests (ICC = 0.57-0.79; p<0.01) in chronologically younger athletes. Building on the results of the first study, which demonstrated a lower reliability of COD tests in younger soccer players, the second study of this thesis (Chapter 4) assessed reliability of alternative COD tests, alongside reliability of an agility test, in an attempt to identify a reliable method of assessment for these characteristics across the entire age range within a youth soccer academy. In addition, relationships between associated physical/reactive qualities and agility performance were assessed. Measures examined within this study demonstrated improved and acceptable reliability comparative to that of the previous study (ICC = 0.82-0.91; CV = 1.5-2.0; d: 0.00-0.08), however, relationships between age (r = -0.28 - r = -0.41) and maturity status (r = -0.39) and between-trial performance differences were observed. Moreover, linear sprint and COD performance demonstrated large to very large relationships with agility performance (r = 0.63-0.71), with reaction time demonstrating small to moderate relationships only (r = 0.22 - 0.38). These findings suggest that physical qualities relate strongly with agility performance within this sample, and that the COD and agility tests adopted within this study possess good between-day reliability, therefore providing meaningful and objective data for monitoring development of youth soccer players. The third experimental study within this thesis (Chapter 5) assessed accuracy between objective (fitness test performance) and subjective (coach rating for corresponding physical quality) measures of physical fitness characteristics relative to youth soccer performance. In addition, considering influence of multiple coaches and practitioners involved within decision making processes throughout youth academy soccer, agreement between lead and assistant coaches was assessed when rating identical players and abilities. Moderate-to-substantial relationships between inter-coach ratings were observed (Omega = 0.48-0.68), however, coach ratings were skewed in nature and only accurate in their ratings of highest and lowest performers. These findings suggest that the translation between objective and subjective assessment methods may be effective when attempting to differentiate between distinct population groups, however this method may lack sensitivity when evaluating homogeneous samples. The final study of this thesis (Chapter 6) investigated differences in age of recruitment, alongside longitudinal performance differences on field-based fitness tests of successful vs. unsuccessful graduates across an entire age spectrum recruited by a professional soccer academy. The majority (68%) of successful players were recruited to the academy at 12-years of age or older, and, successful academy graduates were only observed to physically outperform their "unsuccessful" counterparts from ~13-14 years of age onward, with either no differences in performance, or, performance on physical fitness tests favouring "unsuccessful" players prior to this age. These findings further support the notion that high achievers during childhood and early adolescence may not translate into successful senior professionals and raise question towards predictive and early specialisation models of TI. The studies presented in this thesis will considerably add to the body of research, effectively informing youth soccer practitioners, and enhancing practice around TI and TD.